Conducting a Netnography in Second Language Acquisition Research. Issue 4 (10th July 2021) - Kessler, Matt; De Costa, Peter; Isbell, Daniel R.; Gajasinghe, Kasun
Abstract: In this Methods Showcase Article, we highlight a qualitative research methodology called netnography, an adaptation of ethnography and ethnographic methods applied to researching digital/online communities. We briefly discuss how netnography has evolved from its origins in the fields of consumer research and marketing to its more recent applications in the field of second language acquisition (SLA) for exploring phenomena related to online language teaching and learning. Next, we focus on the specific methods and techniques associated with conducting a netnography, and we propose numerous considerations for SLA researchers who wish to adopt the methodology in future studies. These considerations include various issues such as the recruitment of research participants (e.g., obtaining consent), researcher positioning (e.g., emic perspectives, ethics), the analysis of online multimodal data, and general reporting practices (e.g., protecting participants' identities). Finally, we close with specific recommendations for future research directions. Abstract :